2003
DOI: 10.1055/s-2003-41579
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Balloon Dilation of Gastroenteric Anastomotic Stricture After Laparoscopic Gastric Bypass

Abstract: Stenosis of the gastroenterostomy after laparoscopic gastric bypass occurred in 3.1 % of the patients in this series. It can be successfully and safely treated with endoscopic balloon dilation with good long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 8 publications
5
67
0
6
Order By: Relevance
“…Four studies used a linear stapler only 4,18,22,26 and one study used manual suturing only 11 . One study did not describe the type of stapler 1 . Manual suturing resulted in a higher number of dilations compared with using staplers, but a lower average number of dilations per patient ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies used a linear stapler only 4,18,22,26 and one study used manual suturing only 11 . One study did not describe the type of stapler 1 . Manual suturing resulted in a higher number of dilations compared with using staplers, but a lower average number of dilations per patient ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al 1 reported that they were able to detect endoscopic evidence of stenosis with localized edema and inflammation around the anastomosis, and proposed dilation in patients with these features even if the patients were asymptomatic. There is no consensus regarding the best way to manage stenosis of the gastrojejunal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have obtained good results by Savary-Gilliard bougies (11). Although most prefer the use of through-the-scope (TTS) (4,5,8,10,12,(14)(15)(16)(17)(18). Our experience shows that the dilation of the stenosis of the stoma using TTS balloon is safe and effective.…”
Section: Discussionmentioning
confidence: 78%
“…Published studies are not clear when it comes to describing this aspect. The minority of them clearly manifest not using fluoroscopy during dilation (4,18), others claim to have used it in all or in one of their patients (5,6,8,11,16), and finally, others do not make any sort of comment in this regard in their publications (9,10,14,15,17). Our experience demonstrates that carrying out dilations in patients with stenosis of the anastomosis in the gastric bypass is possible without a fluoroscopic guidance, allowing carrying out the technique in the simplest manner, in the same endoscopy room, without radiation for the patient or for the medical staff, and probably for a shorter period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation